2003
DOI: 10.1248/yakushi.123.1049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Oral Hypoglycemic Agent, Glibenclamide, in a Health Food

Abstract: Glibenclamide, a sulfonylurea derivative (SU) antidiabetic agent was detected in a health food by three diŠerent methods: TLC, HPLC, and liquid chromatography-mass spectrometry (LC MS). For analysis of SU antidiabetics, the sample was extracted with acetone as a sample solution. TLC analysis of the sample solution showed a speciˆc spot that had the same characteristics as those of glibenclamide standard solution. HPLC analysis monitored using a photo-diode array detector showed that the sample solution had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…GLB is commonly used as an oral antidiabetic drug and is sometimes detected in health food. 4) Each powdered solution of GLB tablet was equivalent in weight to one tablet. These samples were independently analyzed with the TLC and HPLC methods.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…GLB is commonly used as an oral antidiabetic drug and is sometimes detected in health food. 4) Each powdered solution of GLB tablet was equivalent in weight to one tablet. These samples were independently analyzed with the TLC and HPLC methods.…”
Section: Applicationsmentioning
confidence: 99%
“…On the other hand, health food advertising weight loss, hypoglycemic effects, and the improvement of sexual dysfunction have a growing market share. Some products are adulterated with synthetic drugs, [1][2][3][4] although natural or herbal materials are stated to be the ingredients. Over the past few years in Japan, several cases have been reported concerning unexpected adverse effects when consumers have consumed health food adulterated with synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) To prevent impairment of health by medicinal ingredients contained in dietary supplements, it is necessary to analyze commercial dietary supplements as thoroughly as possible. Analytical methods are generally required to be highly sensitive, simple, rapid, and low in cost.…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances, unfavorable effects from the consumption of health foods and dietary supplements have been noted. 1,2) Moreover, undesirable pharmacokinetic or pharmacodynamic interactions have been reported with various drugs. [3][4][5][6][7] We also demonstrated that kurosu (Japanese unpolished rice vinegar) is capable of modulating the intestinal absorption of P-glycoprotein (P-gp) substrates.…”
mentioning
confidence: 99%